2018
DOI: 10.22159/ijcpr.2018v10i2.25880
|View full text |Cite
|
Sign up to set email alerts
|

Biological Influence of Methenamine Silver on Broilers

Abstract: Objective: Important trend in the global agribusiness is restrictions of antibiotics content in meat and poultry products. Widespread of antibioticresistant microorganisms leads to huge losses of the effectiveness of the drugs. The aim of the present work was an investigation of the biological activity of antibacterial complex-silver methenamine poultry farming. Methods:The study of biochemical and hematological indices of blood we performed one day after single and course of oral drug administration on broile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The variation in creatinine and urea levels in this study did not exceed normal limits, which suggests that methenamine was possibly non-toxic to the kidneys. This agrees with the result of Evgenii and Vladimi [28] who reported that methenamine silver complex has no toxic effects on blood parameters of broilers.…”
Section: Discussionsupporting
confidence: 93%
“…The variation in creatinine and urea levels in this study did not exceed normal limits, which suggests that methenamine was possibly non-toxic to the kidneys. This agrees with the result of Evgenii and Vladimi [28] who reported that methenamine silver complex has no toxic effects on blood parameters of broilers.…”
Section: Discussionsupporting
confidence: 93%
“…Possible prospects for the use of urotropin are based on the following: 1. Urotropin has antimicrobial activity, so adding it to the culture medium can help preserve biomass from microbial contamination [37]; 2. There are reports that urotropine/glutathione can reduce the cytotoxic effect of sulfur mustard on cultured SVK-14 human keratinocytes in vitro [38].…”
Section: Resultsmentioning
confidence: 99%